Биоморфологическая характеристика пыльцы видов и сортов рода Hemerocallis L. в условиях Донецкого ботанического сада НАН Украины - Крохмаль, И.И. (Промышленная ботаника, 2003)
The morphological peculiarities of pollen of 3 species and 10 varieties of genus Hemerocallis L. have been studied. The wide diversity of the pollen of day-lilies distinguished by its morphological and qualitative parameters has been indicated. The varieties with high percentage of fertile pollen indicative of their to leranse to the regional condition, were determined.